Anti-Inflammatory and Antioxidant Activity of Vitamin E-infused Nanogel Formulation: An In-Vitro Study - Turaga Amani; Mouttoukichenin Surenthar (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Vitamin E, a fat-soluble vitamin, protects cell membranes by scavenging free radicals and reducing lipid peroxidation. It plays a crucial role in immune cell function, gene expression, and modulation of inflammatory mediators. Nanoparticles in drug delivery, particularly chitosan-based nanogels, enhance solubility and prolong biological activity. Objective: This study aims to evaluate the antioxidant and anti-inflammatory activity of a vitamin E-infused nanogel formulation in an in-vitro setting and compare its efficacy with standard antioxidant and anti-inflammatory agents. Methods: A gel was created by lyophilizing 5 g of powdered vitamin E, 0.5 g of chitosan, 0.2 mL of tween 80, and 10 mL of monosodium phosphate in 90 mL of distilled water, which was then heated to 55°C for 30 minutes while stirring. The formulation’s antioxidant and anti-inflammatory activities were assessed using standard assays, such as DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging and albumin denaturation assays. The nanogel’s effectiveness was assessed by comparing its percentage inhibition values at different concentrations with those of standard antioxidants (ascorbic acid) and anti-inflammatory agents (diclofenac sodium). Results: The vitamin E-infused nanogel demonstrated antioxidant and anti-inflammatory properties comparable to standard drugs, with the highest activity observed at 100 µg/mL in both assays. Conclusion: The study demonstrates that the vitamin E-infused nanogel exhibits promising in-vitro antioxidant and anti-inflammatory activities, with inhibition percentages comparable to standard drugs. Further validation through statistical analysis and in-vivo studies is required to confirm its therapeutic potential in managing oral potentially malignant disorders.